Feeding Dairy Cows With “Leftovers” and the Variation in Recovery of Human-Edible Nutrients in Milk - Takiya, Caio S.; Ylioja, Caroline M.; Bennett, Amanda; Davidson, Melissa J.; Sudbeck, Maggie; Wickersham, Tryon A.; VandeHaar, Michael J.; Bradford, Barry J. (Frontiers in Sustainable Food Systems, 2019)
Ruminants can convert feeds unsuitable and unpalatable for humans into milk and meat, and thereby play a key role in food security. Milk production efficiency is usually calculated as the ratio between nutrients secreted in milk and nutrient intake, but this metric does not address concerns about human/livestock feed competition. Our objective was to evaluate effects of diets composed of ecological leftovers (ECO; industrial by-products and feed produced on land unsuitable for human food production) on dairy cattle productivity compared with traditional diets used in the U.S. We also sought to estimate human-edible (HE) nutrient recovery rate (HE inputs vs. milk nutrients) in different scenarios: thrift (all potentially HE ingredients counted as such), choice (ingredients rarely consumed by humans considered not HE), and land use (land used for forage production could be used to grow corn and soybeans for direct human consumption). Experiment 1 evaluated effects of an ECO diet (ECO1), incorporating wheat straw and by-products, on performance of 12 mid-lactation cows in a crossover design with 20-d periods. Experiment 2 evaluated effects of a different ECO diet (ECO2), using winter crop forage and by-products with or without rumen-protected Lys and Met (ECO2-AA), on performance of 12 late-lactation cows in a 3×3 Latin square design with 21-d periods. Both ECO diets were compared to lactation diets typical in North America (CON). Although ECO1 decreased feed efficiency (milk yield ÷ feed intake), feed intake and milk yield were maintained for primiparous cows. ECO1 increased the HE recovery of metabolizable energy (ME) and protein relative to CON1 across all food system scenarios. In Experiment 2, ECO diets significantly decreased feed intake and milk yield, and in the thrift scenario, recovery of ME and protein were worsened by ECO2. All diets resulted in a positive net recovery of HE digestible essential amino acids, and ECO diets further improved recovery. In conclusion, several factors affect recovery of HE nutrients fed to dairy cows, including dietary composition, land use, and human food system assumptions. Depending on these factors, ECO diets can either improve or reduce the efficiency of converting HE nutrients from feeds into milk.